Object Categorization by Learned Universal Visual Dictionary - Winn, John; Criminisi, Antonio; Minka, Tom (2005)
This paper presents a new algorithm for the automatic recognition of object classes from images (categorization). Compact and yet discriminative appearance-based object class models are automatically learned from a set of training images.